The Effectiveness of Team Games Tournament in Improving Students’ Collaborative Abilities - Norfadila B.; Sekar Purbarini Kawuryan; Bambang Saptono (Jurnal Ilmiah Sekolah Dasar, 2024)
The inappropriate application of learning models in the learning process often results in passive student engagement. This study aims to analyze the impact of the Team Games Tournament (TGT) cooperative learning model on students' collaboration skills in classes A6-22 and A7-22. The study employed a quasi-experimental design with a quantitative approach, categorized as experimental research. The population consisted of all students in class A6-22 (control group, 34 students) and A7-22 (experimental group, 33 students). Data collection techniques included validity tests, normality tests, homogeneity tests, and hypothesis testing using the independent sample t-test. The results indicated that the data were normally distributed and homogeneous, with a significant difference between the experimental and control groups. The average score in the experimental group was 61.15, while the control group scored 57.85. Based on the analysis, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted, indicating a significant positive effect of the Team Games Tournament (TGT) learning model on students' collaboration skills. Therefore, the TGT learning model is proven to be more effective than conventional teaching methods in enhancing students' collaboration abilities.